PENERAPAN KODE ETIK JURNALISTIK PADA KATEGORI BERITA HUKUM KRIMINAL PADA SITUS BERITA ONLINE DATARIAU.COM - Fajri "; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is called the “application of the code of journalistic ethics news at the category of criminal law on the site of online news datariau.com” (an analysis study the contents of the application of chapter 4 and chapter 5 the code of journalistic ethics on a website of datariau.com). The study is based on of a unique the website online datariau.com in which contain da’wah article every day. Were given the freedom looking for press , process and spread the word in accordance with the code of journalistic ethics that applied to keep its credibility. A theory that used in this research was models of communication Laswell. As for the purpose of this research is to know the number of news at the category of criminal law who violates the code of journalistic ethics especially in article 4 and article 5 and spiritual service in preaching that has been performing well on the site of online news datariau.comThe Research conducted acquired through study documentation , the study of literature , and sheets of coding Analysis of data done with the quantitative analysis. Analyzing of using analysis the contents of by test realibility using formulas R.Holsty and strengthened by formula Scott pi. Where the it’s 0.75 and results of the test reability CR - 1 & pi = 1 qualified to do this research. Sampling technique that is used is identification random sampling. A theory that used in this research was communication theory Laswell.The news was taken of the months january 2018 up to march 2018 , sample dealing with this research were 77 news. It means the website online datariau.com have implemented the code of journalistic ethics on news writing criminal law, with the percentage apply the code of journalistic ethics is 87,01 % and the percentage offence is 12,99 %.Keyword: Online News, Code Of Etichs Journalistic, Datariau.com